RECORDS ON THE MARGINS: FROM THE MONASTERY LITERARY HERITAGE OF TRESKAVEC - Koviloski, Slavcho (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
On the margins of many church books are written numerous records that bring out information and tell us a story of everyday life of the common man. For this occasion, we explore and present the records on the margins of the monastery Treskavec, Prilep.